2011
DOI: 10.1016/j.ssc.2011.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-induced erasable photochromism in bilayer metal oxide films

Abstract: We demonstrate that optical transmittance of bilayer samples consisting of pyrolytically-coated amorphous Mg-Sn-O and metal-oxide films as In 2 O 3 and SnO 2 decreases upon ultraviolet illumination, which can be recovered by annealing in air at ~300˚C. Spectral, structural, and compositional studies suggest that this photochromic phenomenon is induced by photoelectronic excitation in the Mg-Sn-O film, electron injection into the metal oxide, which becomes negatively charged, and subsequent formation of metalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Terakado et al [2] conducted transmittance measurements and X-ray diffraction (XRD) analysis on samples consisting of magnesium tin oxide (MTO) spin-coated onto indium tin oxide (ITO) substrates, followed by UV irradiation to induce photochromism. Each analysis was performed for ve scenarios: (a) MTO only, (b) ITO only, (c) MTO/ITO (before UV irradiation), (d) MTO/ITO (after UV irradiation), and (e) MTO/ITO (after heating).…”
Section: Introductionmentioning
confidence: 99%
“…Terakado et al [2] conducted transmittance measurements and X-ray diffraction (XRD) analysis on samples consisting of magnesium tin oxide (MTO) spin-coated onto indium tin oxide (ITO) substrates, followed by UV irradiation to induce photochromism. Each analysis was performed for ve scenarios: (a) MTO only, (b) ITO only, (c) MTO/ITO (before UV irradiation), (d) MTO/ITO (after UV irradiation), and (e) MTO/ITO (after heating).…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] In recent years, studies on the use of photochromism utilizing the accumulation of carriers at the trap levels of semiconductors have been performed. 24,25) Furthermore, there have been some reports on the use of batteries using the trap levels of oxide semiconductors. [26][27][28][29] A device of particular interest is the Guera battery, which accumulates carriers at the trap levels of oxide semiconductors formed by UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some researchers speculated that these electrochromic materials could be used in energy-storable solar cells. [32][33][34][35][36][37][38] Terakado et al 39 reported an erasable photochromic bilayer metal oxide film of tin oxide and magnesium oxide. In their paper, they inferred absorption or scattering for electrochromic phenomenon.…”
Section: Introductionmentioning
confidence: 99%